Corpus inscriptionum Iudaeae/Palaestinae a multi-lingual corpus of the inscriptions from Alexander to Muhammad. Volume I, Jerusalem. Part 2, 705-1120 - Cotton, Hannah (Berlin ; New York : De Gruyter, 2012)
Anyone involved in the study of ancient Iudaea/Palaestina and its vicinity has felt the need for a comprehensive work containing all the inscriptions in various languages found in the region. The lack of such a work was all the more regrettable, as the material concerns not only those interested in the region, but also students of a great variety of related subjects, such as the history of the ancient Near East, ancient Jewish history and early Christianity, and, of course, historians of the Hellenistic, Roman and Byzantine periods. The inscriptions are presented within their specific context, and complemented by a translation and commentary; where available, the texts are accompanied by a reproduction.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Jewish inscriptions -- Israel; Inscriptions -- Middle East; HISTORY / Ancient / Greece; Electronic books